Improving Yield of Transplanted Aman and Boro Rice Through Tegra Package of Cultivation (Bangladesh Agronomy Journal, 2016)
The study investigated the yield performance of transplant aman rice cv. BRRI dhan49 and boro rice cv. BRRI dhan29 under improved package of cultivation (TEGRA) as compared to farmers practice. TEGRA is a rice farming practice which includes use of quality seeds and healthy seedlings, transplanting with rice transplanter, use of herbicide, use of balanced fertilization and micronutrients, and preventive plant protection measures. The study during transplant aman season included two treatments on rice cultivation method viz. TEGRA package and farmers practice while in boro rice four treatments viz. TEGRA package, farmers practice with high inputs, farmers practice with medium inputs and farmers practice with low inputs. The yield and plant characters of both transplant aman and boro rice were significantly influenced by the TEGRA package of cultivation as compared to farmers practice. TEGRA package of cultivation as compared to farmers practice increased the grain yield by 18.3% in transplant aman rice and by 80% in boro rice with less cost of production as compared to farmers practice, which eventually resulted 23% increase in gross return and 400% in net return. As a result, the benefit cost ratio of TEGRA package was much higher (1.35 and 2.20 during transplant aman rice and boro rice, respectively) compared to that of farmers practice (1.07 and 1.30).Bangladesh Agron. J. 2015, 18(2): 89-95